Structural integrity of buckled steel pipes - Pournara A.E., Karamanos S.A., Papatheocharis T., Perdikaris P.C. (2015)
Local distortions on steel pipeline wall in the form of buckles may constitute a threat for the structural integrity of the steel pipeline. In the present paper, experimental research supported by numerical simulation is reported to investigate the structural integrity of buckled steel pipes. A series of six (6) full-scale experiments has been carried out on 6-inch X52 pipes, followed by finite element simulations. The buckled steel pipes are subjected to cyclic loading (bending or pressure) in order to estimate their residual strength and remaining fatigue life. The finite element analysis simulates the experimental procedure for each type of deformation and loading case, in order to estimate the local strain distributions at the buckled region. Based on the numerical results, fatigue life is predicted and compared with the experimental results using an appropriate defined damage factor. The results of the present study are aimed at evaluating existing guidelines and methodologies towards appropriate assessment of local wall distortions in steel pipelines. © 2015 by ASME.